The birth and development of the idealized concept of Arcadia in the ancient world - Corso, Antonio (Archaeopress Archaeology, 2022)
Bringing together for the first time all the available evidence for the origination and development of the concept of Arcadia, from the Homeric period to the early Roman Empire, this book brings to light a treasure-trove of evidence, both well-known and obscure or fragmentary, filling a significant gap in the scholarly bibliography.